O ensino de cálculo estequiométrico e a relação com o saber de licenciandos em Química - Ferreira, José Wesley (2019)
Understanding Stoichiometric Calculus (stoichiometry) has been one of the challenges that high school students face in Chemistry, due to factors such as lack of theoretical and methodological investment by the teachers of this discipline. Based on this problem, the emphasis of this research centered on the initial training in different Chemistry undergraduate courses, being the Federal University of Sergipe (UFS) in the São Cristóvão and Itabaiana Campuses, and the Pio Aracaju-Se). The research was based on the theory Relation with the Knowledge of B. Charlot (2000, 2005 and 2013) and other researchers on this subject, in order to analyze the meaning given by future chemistry graduates to the teaching of stoichiometry in high school classes. approach, aiming to identify how the figures of learning to teach Stoichiometric Calculus are established by the research subjects. In addition, dissertations from the Brazilian Digital Library of Theses and Dissertations (BDTD) were used in the area of education on the theme of this research, and articles on Relation with Knowing and Teaching Chemistry, as well as on the approach to teaching of Stoichiometric Calculus. The graduates chosen as the target audience for the research were, specifically, those who were attending one of the internships in their respective Chemical Licensing courses. To complement the data, we also sought to make a documentary analysis of the course proposal of which the subjects are part, as of curricular reference (PNCEM, BNCC). This analysis was expanded using the Taxonomy of Bloom (2010) to identify the Approach on Stoichiometric Calculus in the textbooks of High School Chemistry approved by PNLD, as well as on the YouTube channels on this content. For the methodological procedures, the research was started with a bibliographical survey about studies that approach the subject, followed by the aforementioned documentary analysis and the application of a questionnaire to the subjects. As results obtained, it can be seen that the research subjects perceive that Stoichiometric Calculus is important for high school, especially if it is approached in a contextualized way so that students of high school can associate their daily life with the various situations in which this subject becomes more explicit. However, initial training has not contributed to their ability to teach stoichiometry in this way. Among the singularities, UFS courses stand out in two respects. The first, by the way the students present more elaborate and meaningful answers. The second course stands out for its curricular structure, presenting more workload in the disciplines that involve Stoichiometric Calculus, giving the license holders greater contact with different situations.